Effectiveness and safety of non-vitamin K antagonist oral anticoagulants in Asian patients with atrial fibrillation and valvular heart disease. (3rd April 2021) - Li, Hsing-Jung; Lin, Shin-Yi; Lin, Fang-Ju; Hung, Chi-Sheng; Wang, Chi-Chuan
Abstract: Objective: We compared the effectiveness and safety outcomes of non-vitamin K antagonist oral anticoagulants (NOACs) and warfarin in patients with AF and VHD, as these patients have been partially excluded from clinical trials. Methods: This retrospective cohort study was conducted using the National Health Insurance Research Database in Taiwan. Patients with AF and VHD and above 20 years of age, who were prescribed oral anticoagulants such as warfarin, dabigatran, rivaroxaban, and apixaban, were included. Propensity score matching was performed to balance intergroup differences. The Cox proportional hazards model was used to compare the effectiveness and safety of warfarin and NOACs. Results: We included 5833 NOAC-warfarin pairs, 3001 dabigatran-warfarin pairs and 2595 rivaroxaban-warfarin pairs. Warfarin and NOACs had similar risk of ischemic stroke (hazard ratio [HR], 0.92; 95% confidence interval [CI], 0.79–1.06; p = .25) and bleeding events (HR, 0.90; 95% CI, 0.78–1.02; p = .10). NOACs showed reduced risk of venous thromboembolism, intracranial hemorrhage, and mortality (HR and 95% CI, 0.39 [0.20–0.77], p = .01; 0.62 [0.45–0.84], p < .01; and 0.47 [0.41–0.53], p < .01, respectively). The benefit of NOACs in reducing the risk of venous thromboembolism was mainly driven by dabigatran, and the benefit of reducing the risk of intracranial hemorrhage and mortality was observed in both dabigatran and rivaroxaban users. Conclusions: NOACs had a comparable risk of ischemic stroke and bleeding in patients with AF and VHD, and reduced the risk of venous thromboembolism, intracranial hemorrhage, and mortality, compared to warfarin. Therefore, NOAC is an effective and safe alternative to warfarin in these patients.